SCREENING OF PIROXICAM SELF-NANOEMULSIFYING DRUG DELIVERY SYSTEM (SNEDDS) USING FRACTIONAL FACTORIAL DESIGN - Septiawan Adi Nugroho; Ilham Kuncahyo; Dian Marlina (Jurnal Kimia Riset, 2023)
Piroxicam belongs to BCS class II and has low solubility. Self-nanoemulsifying drug delivery systems (SNEDDS) are considered a potential approach for increasing the solubility and release of piroxicam. This study aimed to select the components and component ratios of piroxicam SNEDDS using fractional factorial design 26-2 (FFD). The variables used in the DFT development of piroxicam SNEDDS are the type and concentration of oil (triacetin and oleic acid), surfactant (kolliphor EL and Tween 60), and co-surfactants (Transcutol and PEG 400). The FFD results showed 16 runs with different proportions of the piroxicam SNEDDS components, which were then characterized by critical parameters including emulsification time, %transmittance, droplet size, and drug loading. The components and component ratios of the PKM SNEDDS were determined using single-factor plot analysis. The results showed that triacetin (oil), kolliphor EL (surfactant), Transcutol (co-surfactant) had the greatest contribution to the formation of piroxicam SNEDDS with an oil ratio range of 11.11–28.57%, surfactant 44.44–77.78%, co-surfactant 11.11–44.44 %.